Optimization of Liquid Organic Fertilizer Production from Tofu Liquid Waste Using EM-4 Activator and Additional Ingredients of Rice Washing Water and Goat Urine - Maryudi, Maryudi; Kurniawan, Lutfi; Astuti, Erna; Yahya, Asdarina (Indonesian Journal of Chemical Engineering, 2024)
Liquid organic fertilizer is organic fertilizer in liquid form which is partly or wholly derived from organic compounds such as plant, animal and industrial waste, either in solid or liquid form. The nutrients contained in it are in the form of a very fine solution so that it is easily absorbed by plants, even the leaves or stems. Organic fertilizer is one solution to restore soil minerals physically, chemically and biologically from the bad effects of synthetic fertilizers. The benefits of liquid organic fertilizer include providing nutrients for plants, improving soil structure, suppressing bacteria that can be detrimental to the soil, and continuous use of soil will improve the physical, chemical and biological properties of the soil as a result being conducive to the environment. In the fermentation process, the role of microbes greatly determines the product produced. The aim of this research is to determine the potential of liquid waste. in the form of liquid organic fertilizer with the addition of goat urine and rice washing water with variations of 15 mL and 30 mL to increase micro and micro nutrients with the bacterial activator EM-4 through a fermentation process. The results of the optimum organic fertilizer content show that the Biological Oxygen Requirement is 969,549 ppm, the Chemical Oxygen Requirement is 14,801.04 ppm and the Total Suspended Solids is 5.360 ppm. Optimal macro nutrient results show Nitrogen 0.2527%, phosphorus 0.1359%, potassium 0.15435%. And the highest degree of acidity (pH) is 4.415. on the first day